KARAKTERISTIK BAKTERI PENYEBAB INFEKSI SALURAN KEMIH, SERTA POLA ANTIBIOTIKA PADA REKAM MEDIK PASIEN PEREMPUAN DEWASA DI RSU SYLVANY BINJAI - NADHILAH SARI NASUTION; ANCE ROSLINA (JURNAL ILMIAH MAKSITEK, 2023)
Urinary tract infection (UTI) is a condition in which germs or microbes grow and multiply in the urinary tract in significant amounts. Urinary Tract Infections can affect both men and women, but Urinary Tract Infections tend to be more common in women because of the shorter urethra in women than in men. The high prevalence of Urinary Tract Infections and the increasing resistance to antibiotics make this research necessary. To determine the characteristics of bacteria that cause urinary tract infections and the pattern of antibiotics in adult female patients at Sylvani Binjai General Hospital. This study used a descriptive method with a cross sectional case study design. Data on female patients diagnosed with Urinary Tract Infections were collected from the medical record section at the Department of Internal Medicine at Sylvani Binjai General Hospital in the period May-October 2021. The majority of female patients diagnosed with urinary tract infections caused by gram-negative bacteria such as Escherichia coli and using ciprofloxacin as therapy